Association between breastfeeding and breathing pattern in children: a sectional study - Teresinha S.P. Lopes; Lúcia F.A.D. Moura; Maria C.M.P. Lima (Elsevier, 2014)
OBJECTIVE: to determine the prevalence of mouth breathing and to associate the history of breastfeeding with breathing patterns in children. METHODS: this was an observational study with 252 children of both genders, aged 30 to 48 months, who participated in a dental care program for mothers and newborns. As an instrument of data collection, a semi-structured questionnaire was administered to the children's mothers assessing the form and duration of breastfeeding and the oral habits of non-nutritive sucking. To determine the breathing patterns that the children had developed, medical history and clinical examination were used. Statistical analysis was conducted to examine the effects of exposure on the primary outcome (mouth breathing), and the prevalence ratio was calculated with a 95% confidence interval. RESULTS: of the total sample, 43.1% of the children were mouth breathers, 48.4% had been breastfed exclusively until six months of age or more, and 27.4% had non-nutritive sucking habits. Statistically significant associations were found for bottle-feeding (p < 0.001) and oral habits of non-nutritive sucking (p = 0.009), with an increased likelihood of children exhibiting a predominantly oral breathing pattern. A statistically significant association was also observed between a longer duration of exclusive breastfeeding and a nasal breathing pattern presented by children. CONCLUSION: an increased duration of exclusive breastfeeding lowers the chances of children exhibiting a predominantly oral breathing pattern.